2002
DOI: 10.1007/s00267-002-2732-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Man-Made Landscape Features on Numbers of Estuarine Waterbirds at Low Tide

Abstract: The potential impact of human disturbance on wintering waterbirds using intertidal mudflats was considered by relating their numbers to the presence of nearby footpaths, roads, railroads, and towns. Data were obtained for six English estuaries from the Wetland Bird Survey Low Tide Count scheme. Counts were undertaken monthly from November to February, and data were available for an average of 2.8 years per estuary for the period 1992-1993 to 1999-2000. Count sections and the positions of man-made landscape fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 0 publications
1
28
0
2
Order By: Relevance
“…Burton et al (2002) pointed out the presence of developed area may cause habitat loss and habitat fragmentation, or bring in human disturbances. Yet developed areas in Yilan occurred in small patches intermingled with other habitat types, and the total percentage of developed area remained low.…”
Section: Landscape Variables and Waterbirdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Burton et al (2002) pointed out the presence of developed area may cause habitat loss and habitat fragmentation, or bring in human disturbances. Yet developed areas in Yilan occurred in small patches intermingled with other habitat types, and the total percentage of developed area remained low.…”
Section: Landscape Variables and Waterbirdsmentioning
confidence: 99%
“…The impact of habitat fragmentation caused by developed areas may be low in our case. The impact of human disturbances may be low because some waterbird species are tolerant to human disturbance (Burton et al 2002). This does not mean an increase in developed area has no negative effect.…”
Section: Landscape Variables and Waterbirdsmentioning
confidence: 99%
See 1 more Smart Citation
“…12, Múrias and colleagues, in a study akin to a BACI design, reported significantly lower shorebird abundances in saltpans close to a new railway that had recently begun to operate. Another study by Burton et al (2002) reported reduced wader abundances in relation to footpaths, roads and railroads, although this greatly varied across species and human structures. Together, these studies suggest that the exclusion effects of railways on wetland birds may be small in some cases but not in others, and thus drawing generalities would require a larger number of studies covering a wide range of socio-ecological contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Traffic volume had a negative effect on breeding with extremely heavy traffic reducing bird presence and breeding up to 1200 m from a road (Forman and Deblinger, 2000). Burton et al (2002) found that persistent disturbance along footpaths, roads, and railroads in Gibbs (1998) was associated with large differences in the ability of amphibians to cross roads and disperse into natural forests in Southern Connecticut. In protected desert landscapes, a direct relationship between bird habitat potential and relative abundance of many species was correlated to the total length of roads and spatial distance (Gutzwiller and Barrow, 2003).…”
Section: Urbanization and Wildlife Habitatsmentioning
confidence: 96%